Discussion - Of Mr. Colby's Paper on Comparison of American and Foreign Rail-Specifications, with a Proposed Standard Specification to Cover American Rails Rolled for Export (see Trans., xxxvii., 576) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1908)
Albert Ladd Colby, New York, N. Y. (communication to the Secretary†):—I observed (Trans., xxxvii., 585) that to obtain tenders from several American mills, the foreign engineer should modify his maximum phosphorus to 0.10 per cent., not as Mr. E. Windsor Richards quotes me, that no American rail-maker can produce rails under 0.10 per cent. of phosphorus. Mr. Richards claims that no English engineer would agree to accept 0.10 per cent. of phosphorus on any terms whatever. Mr. Webster writes that only after an engineer has .been convinced that rails can be made in America equal in every respect to those he is getting abroad, should he be asked to modify ally conditions in his specifications. I know it to be a fact that during recent years in many cases, as, for instance, When delivery could be secured more promptly in the United States than in Europe, the consulting engineers of several British and colonial railroads have frequently agreed to modify their phosphorus requirement to a maximum of 0.10 per cent., and the rails delivered' under these modified specifications have, under like conditions, given just as satisfactory service and proved to be no more brittle than similar sections of 0.07 per cent. phosphorus rails, rolled in England under the same specification except without modification as to phosphorus. Furthermore, it would appear from the analyses of British rails, quoted by E. A. Dancaster,2 in his discussion of Mr.